Pengembangan UKM Aksesoris Mebel dengan Media Pemasaran Teknologi Informasi - Muhammad Imam Ghozali; Wibowo Harry Sugiharto; Zaenal Afifi (Muria Jurnal Layanan Masyarakat, 2020)
The purpose of the community service is to provide training and use IT. Partners in this activity are UKM Cipto Logam. The training stages used are the observation and interview stage, the stage of IT application, the stage of training and mentoring for the use of IT, the stage of collaboration with the government, and the stage of monitoring and evaluation. The result of the activity are : 1) UKM furniture accessories have online marketing media at the level of craftsmen, one of which in the presence of metal copyright sales information system by the craftsmen themselves. 2) UKM furniture accessories have financial management principles in a simple accounting principle so that craftsmen can manage finance neatly.